A New Model for Market-Based Regulation of Subnational Borrowing : The Mexican Approach - Giugale, Marcelo; Korobow, Adam; Webb, Steven (World Bank, Washington, DC, 2015)
Faced with weak sub-national finances that pose a risk to macroeconomic stability, Mexico's federal government in April 2000 established an innovative incentive framework to bring fiscal discipline to state and municipal governments. That framework is based on two pillars: an explicit renunciation of federal bail-outs, and a Basel-consistent link between the capital-risk weighting of bank loans to sub-national governments, and the borrower's credit rating. In theory, this new regulatory arrangement should reduce moral hazard among banks and their state, and municipal clients; differentiate interest rates on the basis of the borrower's creditworthiness; and, elicit a strong demand for institutional development at the sub-national level. But its access will depend on three factors critical to implementation: 1) Whether markets find the federal commitment not to bail out defaulting sub-national governments credible. 2) Whether sub-national governments have access to financing other than bank loans. 3) How well bank capital rules are enforced.